Drawing Theory. An Introduction - Marc Schoonderbeek; Stefano Milani (Footprint)
Nowadays, drawing practices seem to operate in a rather uncertain field that is typical of an in-between phase of disciplinary development and that needs to be addressed, if an ‘anticipated projection’ of the development of drawing is to be attempted. The field of drawing, as practice and discourse, seems to have entered an end-condition, where the celebration of the extensive production of drawings is combined with a certain fatigue in both its understanding and reflection. Even though the role of drawing is nowadays still regarded as the most common act of architecture, this understanding of drawing is hardly subject to critical inquiries, and, unfortunately, mostly limited to its instrumental role within the representation of the project.A common characteristic in all of the papers in this issue of Footprint is that a specific character of the theoretical field generated by drawing is the elaboration of the correlation between two epistemic regions. This singular character probably belongs to drawing’s structural duality of being simultaneously a simulacrum of a reality and reality itself, memory and anticipation, subject and object, by being in essence the measure of two different facets inherent to architectural thinking. Drawing not only gives consistency to the poles, rendering them architectural matter, but also literally (re)constructs them. At the same time, drawing formalizes the theoretical distance between the two.